Peningkatan Kesiapsiagaan Bencana Melalui Teknologi AR di Sekolah Dasar Tilongkabila - I Made Hermanto; Huzaima Mas’ud; Icha Untari Meidji (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service program aims to enhance disaster preparedness among elementary school students in Tilongkabila District, Gorontalo, an area prone to various natural disasters such as earthquakes, tsunamis, and liquefaction. The AR application developed allows students to understand the phenomena of natural disasters in a visual and interactive way, with three-dimensional visualizations and mitigation steps to be taken. An initial socialization on the disaster application based on AR was conducted, involving over 80% of the teachers and 40 students from elementary schools in Tilongkabila. The activity aimed to increase their understanding and skills in facing disasters, as well as to use the AR application effectively. This socialization also introduced how to use the application in learning, providing participants with direct experience interacting with the developed technology. Findings from the implementation indicate a substantial improvement in teachers’ understanding of the use of the AR-based disaster mitigation application, with a normalized gain (g) of 0.96, classified as very high. Additional results also show an increase in students’ knowledge related to disaster literacy. The program has cultivated a stronger culture of disaster preparedness within schools and surrounding communities.